Unraveling an FNR based regulatory circuit in Paracoccus denitrificans using a proteomics-based approach - Bouchal, Pavel; Struhárová, Iva; Budinská, Eva; Sedo, Ondrej; Vyhlídalová, Tereza; Zdráhal, Zbynek; van Spanning, Rob; Kucera, Igor (Biochimica et biophysica acta, 2010)
The switch from aerobic to anaerobic respiration in the bacterium Paracoccus denitrificans is orchestrated by the action of three FNR-type transcription regulators FnrP, NNR and NarR, which are sensors for oxygen, nitric oxide and nitrite, respectively. In this work, we analyzed the protein composition of four strains (wild type, FnrP-, NNR- and NarR-mutant strains) grown aerobically, semiaerobically and semiaerobically in the presence of nitrate to discover the global role of FNR-family transcription regulators using proteomics, with data validation at the transcript and genome levels. Expression profiles were acquired using two-dimensional gel electrophoresis for 737 protein spots, in which 640 proteins were identified using mass spectrometry. The annotated 2-D proteome map provided the most comprehensive coverage of P. denitrificans proteome available to-date and can be accessed on-line at http://www.mpiib-berlin.mpg.de/2D-PAGE/. Our results revealed several types of regulation under the conditions tested: (1) FnrP-controlled regulation of nitrous oxide reductase, UspA and OmpW as confirmed at protein, transcript and DNA level (position of FNR boxes). (2) Proteins regulated via additional regulators, including proteins involved in NNR and NarR regulons: nitrate reductase beta-subunit, TonB-dependent receptors, nitrite reductase, a TenA-type transcription regulator, and an unknown protein with an alpha/beta hydrolase fold. (3) Proteins whose expression was affected mainly by the growth condition. This group contains SSU ribosomal protein S305 / sigma(54) modulation protein, and two short-chain reductase-dehydrogenase proteins.
Keywords: dusitany; anaerobióza; proteomika; Gene Expression Regulation, Bacterial; aerobióza; Aerobiosis; Transcription Factors; Anaerobiosis; Transcription, Genetic; genetická transkripce; Bacterial Proteins; transkripční faktory; kyslík; Proteomics; Paracoccus denitrificans; oxid dusnatý; Nitric Oxide; regulace genové exprese u bakterií; Oxygen; bakteriální proteiny; Nitrites